2019
DOI: 10.54687/jurnalkajenv03i01.4
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH EKSTRAK BIJI BUAH KEBEN (Barringtonia asiatica) DALAM PROSES IMOTILISASI PADA TRANSPORTASI SISTEM TERTUTUP BENIH IKAN KAKAP PUTIH (Lates calcarifer)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak buah keben yang dapat digunakan sebagai obat bius untuk bass laut dan mengetahui konsentrasi ekstrak buah keben dalam proses mencengangkan yang memberikan daya tahan tertinggi benih bass laut. Metode eksperimental digunakan dalam penelitian ini dengan Rancangan Acak Lengkap (RAL) yang terdiri dari 5 perlakuan dosis: 0 mg / l; 5 mg / l; 10mg / l; 15 mg / l dan 20 mg / l dengan 3 ulangan. Data dianalisis menggunakan analisis varians, normalitas pertama d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The high market demand that demands continuity of production, but there are several obstacles in the field that affect the amount of production. Monica & Mardiana (2019) found that survival rate of white snapper transportation without anesthesia about 70%.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high market demand that demands continuity of production, but there are several obstacles in the field that affect the amount of production. Monica & Mardiana (2019) found that survival rate of white snapper transportation without anesthesia about 70%.…”
Section: Introductionmentioning
confidence: 98%
“…Constraints that are often faced by white snapper hatcheries are damage to packing packaging due to punctured dorsal fin spines, changes in water quality during transportation, such as decreased O2 in water media, increased CO2 which causes stress fish so that the survival rate of the seeds is low (Monica et al, 2019). The most influential factor in the transportation of live fish is water quality, namely physical and chemical parameters of water, such as dissolved oxygen, temperature, pH, carbon dioxide, and ammonia (NH3) which causes fish to become stressed (Supriyono et al, 2010).…”
Section: Introductionmentioning
confidence: 99%